Somatic hypermutation shapes the viral escape profile of SARS-CoV-2 neutralising antibodiesResearch in context - Matthias Bruhn; Maureen Obara; Mariana Gonzalez-Hernandez; Wencke Reineking; Abdus Salam; Monica Mirolo; Imke Hinrichs; AhmedElmontaser Mergani; Yannic Bartsch; Axel Schambach; Gert Zimmer; Wolfgang Baumgärtner; et al. (EBioMedicine)
Summary: Background: Since the onset of the COVID-19 pandemic, SARS-CoV-2 neutralising monoclonal antibodies (mAbs) are being developed for clinical use. With the appearance of new virus variants, most mAbs lost their virus-neutralising activity, highlighting the complexity of mAb development under conditions of continuous SARS-CoV-2 evolution. Methods: Hamsters were treated with SARS-CoV-2 neutralising mAbs and then challenged with SARS-CoV-2. Recombinant VSV expressing the spike protein of SARS-CoV-2 was utilised in an in vitro system to select for antibody escape variants. Surface plasmon resonance measurements were performed to characterise the binding affinity and epitope of various mAbs. Fc-mediated effector functions of neutralising and non-neutralising mAb combinations were determined via multiple in vitro assays. Findings: Few of the mAb treated and infected hamsters experienced breakthrough infections, which derived from mutated virus that emerged in vivo. We developed an in vitro antibody escape assay that recapitulated the in vivo situation and we found that somatic hypermutations (SHM) affected the profile of viral escape hotspots that mAbs selected for. Pairwise combination of mAbs binding non-overlapping epitopes suppressed the emergence of viral mutants. The formulation with a third, non-neutralising mAb enhanced the Fc-mediated effector functions of the mAb treatment in an additive manner. Interpretation: We conclude that treatment with single mAbs rapidly leads to the formation of novel virus variants. An important function of SHM is to suppress the emergence of viral antibody escape variants. Our data suggest that the anticipatory B cell memory can be harnessed to design combinations of SARS-CoV-2 neutralising mAbs that have a reduced risk to induce viral escape. Funding: This study was supported by public funding from the German Research Foundation (DFG), the Federal Ministry of Education and Research (BMBF), the COVID-19-Research Network of the State of Lower Saxony (COFONI), the German Centre for Infection Research (DZIF), and the Helmholtz Association of German Research Centres.